Eye Movements during Art Appreciation by Students Taking a Photo Creation Course - Ishiguro, Chiaki; Yokosawa, Kazuhiko; Okada, Takeshi (Frontiers in Psychology, 2016)
Previous studies have focused on the differences in the art appreciation process between individuals, and indicated that novice viewers of artworks, in comparison to experts, rarely consider the creation process of the artwork or how this may relate to style. However, behavioral changes in individuals after educational interventions have not been examined. Art education researchers claim that technical knowledge and creation experiences help novice viewers to pay attention to technical features of artwork. Therefore, an artistic photo creation course was designed and conducted to help students acquire techniques and procedural knowledge of photo creation. The present study verified whether students’ viewing strategies during appreciation of photographs changed after the course. Twenty-one students participated in two sessions, viewing the same 12 photographs before and after the course. Based on the analysis of recorded eye movements, the results indicated that the students’ perceptual exploration became more active with photographs containing recognizable subjects (i.e., humans and objects), and their global saccades increased when they viewed classic photography, one of the categories of photography covered in the course. Interview data after the course indicated that students became aware of the technical effects in photographs. These results suggest that students’ viewing strategies may change following a course, as assessed by behavioral measures of eye movements. Further examination is needed to validate this approach to educational effect measurement.